Management of Calcific metamorphosis by conventional Root Canal Treatment. A case report - Mahmud, Kazi Hossain; Iqbal, Md Ashif; Talukder, Fida Hasan (Update Dental College Journal, 2020)
The calcified root canals cause many problems during endodontic treatment due to difficulty in canal orifice location, negotiation, preparation as well as consideration of operating time. Most serious problem may arise during any phase of root canal treatment procedure even taking a lot of precaution. Partial or total obliteration of pulpal chamber or root canal space is the most common consequences of a tooth which is exposed to traumatic injury. The most common presentation of such a tooth is complete or partial loss of the pulp space radiographically and discoloration particularly yellow discoloration of the clinical crown. Around 7–27% of teeth having the feature of partial canal calcification shows features of pulp necrosis accompanied by radiographic signs of chronic periapical periodontitis. Very low numbers of teeth( 2-3%) may present with total obliteration of pulp chamber and the root canal system . Teeth with such features is challenging to provide a successful root canal treatment; . In this case report a 21 years old female patient attended with complaints of discoloration , mild spontaneous pain , and several episodes of gingival swelling with history of trauma four years back in her both maxillary central incisors. The case was evaluated clinico radiographically and the diagnosis was a case of calcification both maxillary central incisors. Root canal treatment to manage the calcified canals following conventional technique was planned . After treatment patient was free from subjective and objective signs and symptoms and she was advised for periodic follow-up Update Dent. Coll. j: 2020; 10 (2): 21-25